Identity of Euploea orontobates Fruhstorfer, 1910 (Lepidoptera: Nymphalidae), a milkweed butterfly from Thailand and Vietnam - Monastyrskii, A. L.; Vane-Wright, R. I. (Zootaxa, 2009)
Euploea orontobates Fruhstorfer, 1910, described from south-eastern Thailand (Si Racha district), is demonstrated to be a senior synonym of Euploea conbuom Saito & Inayoshi, 2006, from southern Central Vietnam. The relationships and biogeography of this rare butterfly are discussed, and presented together with comments on the principal mimicry complex among the Euploea species of Indochina.